2021
DOI: 10.3390/ijerph18189484
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Harm Reduction Interventions for Adult Gambling at the Local Level: An Umbrella Review of Empirical Evidence

Abstract: Concerns about negative consequences of gambling diffusion are increasing. Prevention and harm reduction strategies play a crucial role in reducing gambling supply and harms. This study aims to conduct an umbrella review of the effectiveness of gambling preventive and harm reduction strategies, which can be implemented at a local level and targeted at adults. It was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Sixteen reviews were analyzed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…While the results are not statistically representative, they are revealing of the Finnish gambling field. In line with existing evidence of effective harm prevention (e.g., Fiskaali et al, 2023; Velasco et al, 2021), the most often mentioned means of preventing harms according to Russian speakers were public health-oriented measures that target the full population rather than just those who actively gamble. These include information on harms and reducing the visibility and availability of gambling and gambling marketing.…”
Section: An Outside View Helps In Implementing More Effective Preventionmentioning
confidence: 78%
“…While the results are not statistically representative, they are revealing of the Finnish gambling field. In line with existing evidence of effective harm prevention (e.g., Fiskaali et al, 2023; Velasco et al, 2021), the most often mentioned means of preventing harms according to Russian speakers were public health-oriented measures that target the full population rather than just those who actively gamble. These include information on harms and reducing the visibility and availability of gambling and gambling marketing.…”
Section: An Outside View Helps In Implementing More Effective Preventionmentioning
confidence: 78%
“…Much research has been conducted on the effectiveness of harm reduction and harm prevention efforts in land-based gambling, including several systematic reviews and a recent umbrella review [see 17 22 ]. These studies have shown that many harm prevention and harm reduction efforts can reduce consumption or harms in land-based environments, although effectiveness depends largely on implementation and how effects are measured.…”
Section: Introductionmentioning
confidence: 99%
“…Based on available research focussing mainly on land-based gambling, limiting availability and accessibility are among the most effective means to reduce total consumption. Availability-related measures include limiting the number of venues, venue hours, or access to cash or credit, as well as limiting accessibility with for example age limits [ 15 , 17 20 , 23 ]. Smoking bans and bans on the sale of alcohol in gambling venues have also led to reduced gambling consumption [ 15 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hingegen fanden bereits einige Maßnahmen, deren Evidenz als belegt angesehen werden kann, keinen Eingang in den GlüStV. Beispielhaft sei in diesem Zusammenhang die Beschränkung der Verfügbarkeit von Glücksspielen genannt, die eine effektive Strategie sowohl für die universelle Prävention (Allgemeinbevölkerung) als auch für die selektive Prävention (Risikogruppen) darstellt [2]. Gleichwohl wurde der Glücksspielmarkt in Deutschland mit Inkrafttreten des neuen GlüStV liberalisiert.…”
Section: Introductionunclassified